Formulation And Physical Characteristic Of Hard Candy Lozenge Of Citrus Limon Essential Oil On Various Types Of Sugar Free Candy Base (Isomalt, Mannitol, Sorbitol) - Nawatila, Roisah; Azminah (Brawijaya University, 2024)
Citrus limon is a natural ingredient that has potential as an anti-anxiety. The effect of increasing dopamine on the brain barrier due to consuming citrus limon essential oil can help relieve stress, fatigue, dizziness, and anxiety. This study aims to formulate citrus limon essential oil hard candy lozenge with various types of sugar free candy bases and evaluate its effect on the physical characteristic of the lozenge. Previously, this study was preceded by identifying the D-Limonene compounds as an active material on the citrus limon essential oil using the GC-MS method. There are three formulas used in this study, including F1 (isomalt), F2 (mannitol), and F3 (sorbitol). Physical characteristic tests carried out include organoleptics, weight variations, dimension, hardness, friability, dissolved pH, dissolve time, and hedonic tests. The identification test of citrus limon essential oil showed the presence of D-Limonene compound, in accordance with CoA and comparative literature. Thus, it can be concluded that the raw material of the oil used in this study was in accordance with the established quality. In addition, the results of physical characteristic showed that the organoleptic test of F1 and F3 yields better results than F2 (murky white color and rough texture). In addition, the evaluation of weight variation, friability, and dissolve time of F1 and F3 met specifications, while F2 did not meet specifications. Therefore, the sugar free candy base that can be developed into a hard candy lozenge in this study was by using isomalt (F1) and sorbitol (F3).